Beyond the association. Toxoplasma gondii in schizophrenia, bipolar disorder, and addiction: systematic review and meta‐analysis. (15th April 2015) - Sutterland, A. L.; Fond, G.; Kuin, A.; Koeter, M. W. J.; Lutter, R.; van Gool, T.; Yolken, R.; Szoke, A.; Leboyer, M.; de Haan, L.; Leboyer, Marion
<x xml:space="preserve">Abstract</x> Objective To perform a meta‐analysis on studies reporting prevalence of Toxoplasma gondii (T. gondii) infection in any psychiatric disorder compared with healthy controls. Our secondary objective was to analyze factors possibly moderating heterogeneity. Method A systematic search was performed to identify studies into T. gondii infection for all major psychiatric disorders versus healthy controls. Methodological quality, publication bias, and possible moderators were assessed. Results A total of 2866 citations were retrieved and 50 studies finally included. Significant odds ratios (ORs) with IgG antibodies were found in schizophrenia (OR 1.81, P < 0.00001), bipolar disorder (OR 1.52, P = 0.02), obsessive–compulsive disorder (OR 3.4, P < 0.001), and addiction (OR 1.91, P < 0.00001), but not for major depression (OR 1.21, P = 0.28). Exploration of the association between T. gondii and schizophrenia yielded a significant effect of seropositivity before onset and serointensity, but not IgM antibodies or gender. The amplitude of the OR was influenced by region and general seroprevalence. Moderators together accounted for 56% of the observed variance in study effects. After controlling for publication bias, the adjusted OR (1.43) in schizophrenia remained significant. Conclusion These findings suggest that T. gondii infection is associated with several psychiatric disorders and that in schizophrenia reactivation of latent T. gondii infection may occur.